THE IMPACT OF THYROID STIMULATING HORMONE (TSH), TOTAL THYROXINE (TT4) AND URINARY IODINE CONCENTRATION (UIC) ON NEONATAL OUTCOME AND PRETERM DELIVERY - Maja Avramovska; Borislav Karanfilski; Vaskova, Olivija; Dimitrov, Goran; Tofoski, Gligor; Dzikova, Elena; Nikoloska, Katerina; Daneva Markova, Ana; Shikole, Aleksandar (Македонско лекарско друштво = Macedonian Medical Association, 2020)
Introduction. Impaired maternal thyroid metabolism is associated with poor outcomes for the mother, the developing newborn and preterm delivery. The aim of this study was to investigate the impact of thyroid stimulating hormone (TSH), total thyroxine (TT4) and urinary iodine concentration (UIC) on neonatal outcome and preterm delivery. Methods. From the cohort of 358 healthy pregnant women (mean age 30.15±5.26 years)three subgroups were formed accordingto gestational week of pregnancy. TSH and TT4 were analyzed with time-resolved fluoroimmunoassay and UIC by mass spectrometry. Correlation of thyroid parameters with other variables was analyzed by Pierson’s correlation test. Logistic regressionwas used to predict the neonatal outcome and preterm delivery. Receiver operating characteristics curve analysis was used to calculate cut-off value of TT4 as predictors of treating preterm delivery (TPD). Results. There was a statistically significant difference in TSH (0.471±0.82 mIU/L vs. 0.544±0.337 mIU/L, P=0.016) betweenprematurely delivered and delivered atterm. TSH had a statistically significant predictive impact on the !PD in the second trimester (Exp &=-0.0532, Wald=4.6003, P=0.032). TT4 assumed a predictive impact in thethird trimester (Exp &=1.0227, Wald=6.0254, P=0.014). The cut-off point of TT4 in detecting of TPD was131.3 nmol/L, area under the curve =0.66. Conclusion. The results of this study suggest that values of maternal TT4 and TSH show possible predictive impact of preterm birthin the second and third trimester, which varies by gestational age.
Keywords: thyroid stimulating hormone; total thyroxine; urinary iodine concentration; preterm delivery